2009
DOI: 10.1111/j.1582-4934.2008.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

One carbon metabolism disturbances and the C677T MTHFR gene polymorphism in children with autism spectrum disorders

Abstract: Autism spectrum disorders (ASDs), which include the prototypic autistic disorder (AD), Asperger’s syndrome (AS) and pervasive developmental disorders not otherwise specified (PDD-NOS), are complex neurodevelopmental conditions of unknown aetiology. The current study investigated the metabolites in the methionine cycle, the transsulphuration pathway, folate, vitamin B12 and the C677T polymorphism of the MTHFR gene in three groups of children diagnosed with AD (n= 15), AS (n= 5) and PDD-NOS (n= 19) and their age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 47 publications
6
89
0
Order By: Relevance
“…MTHFR and OCM play key roles in physiologic processes by regulating the channeling of onecarbon units between the DNA cycle (nucleotide synthesis) and the methylation cycle (Frankenburg, 2007;Krebs et al, 2009;Laanpere et al, 2010). Dysfunction of the OCM cycle has been linked to neural tube defects (van der Put et al, 2001;Zhang et al, 2008) and autism (Pasca et al, 2009), and may contribute to the pathogenesis of other disorders, including leukemia (de Jonge et al, 2009;Wiemels et al, 2001), dementia (Kim et al, 2008;Kronenberg et al, 2009), colorectal cancer (Kim, 1999;Levine et al, 2010), cardiovascular disease (Smulders and Stehouwer, 2005) and congenital abnormalities (Carmichael et al, 2009;Wani et al, 2008). Given MTHFR's essential role in brain function and neurodevelopment (del Rio Garcia et al, 2009;Ueland et al, 2001), and that family and twin studies have demonstrated considerable shared genetic variance between psychiatric disorders (Cardno et al, 2002;Lichtenstein et al, 2009;McGuffin et al, 2003;Van Snellenberg and de Candia, 2009), it is reasonable to hypothesize that genetic variation in MTHFR may contribute to the shared genetic vulnerability of common psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…MTHFR and OCM play key roles in physiologic processes by regulating the channeling of onecarbon units between the DNA cycle (nucleotide synthesis) and the methylation cycle (Frankenburg, 2007;Krebs et al, 2009;Laanpere et al, 2010). Dysfunction of the OCM cycle has been linked to neural tube defects (van der Put et al, 2001;Zhang et al, 2008) and autism (Pasca et al, 2009), and may contribute to the pathogenesis of other disorders, including leukemia (de Jonge et al, 2009;Wiemels et al, 2001), dementia (Kim et al, 2008;Kronenberg et al, 2009), colorectal cancer (Kim, 1999;Levine et al, 2010), cardiovascular disease (Smulders and Stehouwer, 2005) and congenital abnormalities (Carmichael et al, 2009;Wani et al, 2008). Given MTHFR's essential role in brain function and neurodevelopment (del Rio Garcia et al, 2009;Ueland et al, 2001), and that family and twin studies have demonstrated considerable shared genetic variance between psychiatric disorders (Cardno et al, 2002;Lichtenstein et al, 2009;McGuffin et al, 2003;Van Snellenberg and de Candia, 2009), it is reasonable to hypothesize that genetic variation in MTHFR may contribute to the shared genetic vulnerability of common psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the MTHFR gene analysis show a normal distribution of C677T polymorphism in children with ASDs, but the frequency of the 677T allele was slightly more prevalent in autistic disorder (AD) patients. This study indicates a possible role for the alterations in carbon metabolism in the pathophysiology of ASDs, and provides preliminary evidence for metabolic and genetic differences between clinical subtypes of ASDs [32]. The T allele has been shown to be more prevalent in children with ASD (42.9%) compared with controls (32.3%).…”
Section: Discussionmentioning
confidence: 91%
“…In 2012, using meta-analysis method, Frustaci et al [185] reported that for the C677T allele in the methylene tetrahydrofolate reductase (MTHFR) gene, homozygous mutant subjects (TT) showed a meta-OR of 2.26 (95% confidence interval 1.30-3.91) of being affected by ASD with respect to the homozygous non mutant (CC). Additional single nucleotide polymorphisms (SNPs) in other genes encoding enzymes involved in oxidative stress, such as, have also been associated with a change in ASD risk from several case-control and linkage studies [186][187][188][189][190]. Thus, in the pathogenesis of ASD, oxidative stress may play an important role via neurodegeneration in genetically predisposed individuals.…”
Section: Genes Involved In Neurodegenerationmentioning
confidence: 99%